Minority Religions and the Religion Clauses - Thomas C. Berg (Washington University Law Quarterly, 2004)
Part I of the Article offers reasons why the protection of minority religions should be an important consideration in interpreting the Religion Clauses. Part II then addresses various difficulties and complications in the idea of protecting minority faiths. In addition to the fact that the constitutional text protects all religious faiths, there are difficulties in the effort to define which faiths are minorities. Because of America’s complex patterns of religious identities, who is a minority will often vary depending on the geographical location, on the institutional setting in which a particular legal issue arises, and on how one chooses the key religious differences that sort groups into different categories. Given these difficulties, courts generally should not try to single out certain groups as religious minorities and treat them differently than other groups. Such an approach is too subjective and contestable, in addition to its possible inconsistency with the constitutional text. The only defensible method is to develop principles for various categories of cases that are applicable to all faiths—but that tend to protect whoever happens to be a minority in the given geographical location, institution, or cultural atmosphere. The courts should not undertake to determine who is a minority in a particular case, but should follow rules structurally designed to protect whoever happens to be the minority. Part III then develops such principles for the leading categories of Religion Clause disputes. On many issues I agree with previous commentators about the implications of a minority-protection approach. To ensure that religious minorities enjoy the right to practice their faith, courts should read the Free Exercise Clause expansively and should, in some cases, exempt religiously motivated conduct from laws that impose significant burdens on the conduct. I thus follow other commentators in criticizing the Supreme Court’s rejection of exemptions in Smith. And under a minority-protection approach, the Establishment Clause should be vigorously interpreted to restrict government-sponsored religious exercises and displays in public schools and other government institutions. Such practices by their nature tend to favor the majority religion and impose burdens on dissenters; and the strict separationist approach that has invalidated these practices is best justified by the rationale of protecting religious minorities.
Keywords: Religious minorities; Free exercise clause (Constitutional law); Establishment clause (Constitutional law); Church and state; Freedom of religion